Educational Intervention on Pediatricians’ Knowledge, Attitude and Practice on Child Oral Health: A Hospital Based Longitudinal Study - Shrestha, Sneha; Koirala, Bandana; Shah, Gauri Shankar; Kumar, Abhishek; Baral, Dharanidhar (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: Pediatricians provide multiple early childhood screenings and are in a privileged position to promote child oral health by enacting timely dental referrals. Our primary objective included assessing the pre- and post- educational intervention knowledge, attitude and practice of pediatricians on child oral health. The secondary objective included the assessment of prevalence of oral health problems in children attending Pediatrics out-patient department (OPD).Methods: This one-year hospital based longitudinal study involved conveniently selected 400 children (6 months to 14-years-old) from Pediatrics OPD and 12 pediatricians (complete enumeration) from a university hospital, BPKIHS, Dharan, Nepal. Screening for oral health problems in children was performed. Pre- and post-educational intervention knowledge and attitude towards child oral health of the pediatricians were assessed using a validated questionnaire. The practice component was assessed through pre- questionnaire and pre- and post-intervention dental referral paper practice. Data analysis included descriptive statistics, chi-square and paired t-tests.Results: Educational intervention significantly increased the knowledge score of the pediatricians but not their attitude (p = 0.72) or the paper dental referral practice. Oral health problems were observed in 59.3% of the children attending pediatrics OPD, dental caries being the most prevalent (49.9%).Conclusion: More than half of the children attending pediatrics OPD had oral health problems. Educational intervention was effective in improving pediatricians’ knowledge but not their attitude and the paper dental referral practice.